Imam Syafii pejuang kebenaran / Abdul Latip Talib ; editor, Izmir Azlam, Hijrah Ahmad, Adhika Prasetya - ABDUL LATIP TALIB; Izmir Azlam; Hijrah Ahmad; Adhika Prasetya (Erlangga, 2013)
xxv, 277 hlm. ; 21 cm